Mass Communication Research in Promoting Information Channels - Siddiqui, Taha (International Journal of Control and Automation, 2018)
This study set out to answer the question, "What function does mass communication have in developing countries?" Mass media are the channels used in the process of mass communication, which is the gathering, transmission, and reception of information for large groups of people. From newspapers and television to billboards and smartphones, the range of mass media is vast. From monitoring and correlation to cultural transmission and popular amusement and mobilization and validation, the mass media play an important role in modern society. In addition to these roles, promoting national development is an unavoidable function of the mass media for both advanced and developing countries. Leading institutions throughout the globe, such as the Food and Agriculture Organization and the United Nations Development Programme, have all recognized that the media play a crucial role in human development by promoting education, employment, and equality. Based on this literature review, it is clear that the relationship between media and development in the context of underdeveloped nations has received the least attention. So, the current research was set up to assess how the media encourages growth in South Asia’s emerging nations. The aforementioned nations together with Nepal and Bhutan were chosen.